2021
DOI: 10.1094/pdis-02-21-0241-re
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Analysis and Copper Ion Resistance Detection of 60 Xanthomonas arboricola pv. juglandis Isolates from China

Abstract: Walnut bacterial blight caused by Xanthomonas arboricola pv. juglandis (Xaj) has serious repercussions for walnut production around the world. Between 2015 and 2017, disease samples were collected from six counties (Danjiangkou, Baokang, Suizhou, Shennongjia, Zigui, and Xingshan) in Hubei province, China. Fifty-nine Xaj strains were identified by morphology and specific PCR primers from 206 isolates. The genetic diversity of 60 Xaj strains (59 from Hubei plus one from Beijing) was evaluated by Multilocus Seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Picking up those colonies that have characteristics consistent with typical Xaj morphology, purifying every single representative colony (Xaj suspected) from the independent sample several times. Sixty isolates identified as Xaj (Fu et al 2021) were cultured on YPGA medium at 26℃ for 3 days, and then stored at -80°C within 30% glycerol for future use.…”
Section: Resultsmentioning
confidence: 99%
“…Picking up those colonies that have characteristics consistent with typical Xaj morphology, purifying every single representative colony (Xaj suspected) from the independent sample several times. Sixty isolates identified as Xaj (Fu et al 2021) were cultured on YPGA medium at 26℃ for 3 days, and then stored at -80°C within 30% glycerol for future use.…”
Section: Resultsmentioning
confidence: 99%
“…Using a Cu 2+ concentration of 125 µg/mL (0.5 mM) as the threshold dose, Fu et al (2021) categorized X. arboricola pv. juglandis isolates into resistant and sensitive groups [33]. Previous studies have reported that only some of the studied strains of plant pathogenic bacteria were copper-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…The gyrB sequences were highly conserved, with the same sequence from 60 X. arboricola pv. juglandis isolates from China [33]. The genetic diversity analysis of 59 X. arboricola pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing demand for walnut has led to the growing area of walnut cultivation, and walnut pests and diseases are becoming more frequent. Among them, walnut bacterial blight occurs continuously in many places which is widely distributed in walnut producing areas of many cities in China, and is also found in most walnut producing regions in the world (Fu et al 2021;Kim et al 2021;Sagawa et al 2021). This disease is severely harmful to walnut, affecting the healthy development of the walnut industry.…”
Section: Introductionmentioning
confidence: 99%